Giant Magnetoresistance in the Half‐Metallic Double‐Perovskite Ferrimagnet Mn2FeReO6. (31st July 2015) - Li, Man‐Rong; Retuerto, Maria; Deng, Zheng; Stephens, Peter W.; Croft, Mark; Huang, Qingzhen; Wu, Hui; Deng, Xiaoyu; Kotliar, Gabriel; Sánchez‐Benítez, Javier; Hadermann, Joke; Walker, David; et al.
Abstract The first transition‐metal‐only double perovskite compound, Mn2+2Fe3+Re5+O6, with 17 unpaired d electrons displays ferrimagnetic ordering up to 520 K and a giant positive magnetoresistance of up to 220 % at 5 K and 8 T. These properties result from the ferrimagnetically coupled Fe and Re sublattice and are affected by a two‐to‐one magnetic‐structure transition of the Mn sublattice when a magnetic field is applied. Theoretical calculations indicate that the half‐metallic state can be mainly attributed to the spin polarization of the Fe and Re sites.